The prevalence of gamma-hydroxybutyrate (GHB) in motor vehicle drivers and its co-administration with amphetamine type substances (ATS) in Queensland, Australia (2011–2018). (October 2019) - Griffiths, Andrew; Hadley, Lenore
Highlights: Analysis for GHB was performed on over 15, 000 blood specimens collected from motor vehicle drivers in Queensland, Australia (2011–2018). GHB was identified in 160 specimens or 1.1% of samples received. GHB was very commonly co-consumed with amphetamine type substances (91%). GHB use was predominantly identified in drivers from city areas with a geographical localisation in the Gold Coast region. Abstract: The routine analysis of driver specimens for gamma-hydroxybutyrate (GHB) is rarely performed by toxicology laboratories as the physical and chemical properties of GHB make it unamenable to the screening methods usually employed. The prevalence of the drug in driver populations has therefore only rarely been reported. This study outlines the results of the routine analysis for GHB in the blood of motor vehicle drivers in Queensland, Australia, over an eight-year period (2011–2018). The methodology for GHB analysis was updated over the course of the study; screening for GHB was conducted using GC/FID or GC/MS between 2011 and 2016 and by LC/MS/MS from 2017 onwards. Due to the endogenous nature of GHB, any specimens containing greater than 5 mg/kg GHB were subjected to quantitative analysis by either; GC/MS after liquid-liquid extraction and derivatisation with BSTFA + 1%TMCS (2011–2016), or by LC/MS/MS analysis after solvent precipitation from 2017 onwards. Of the 15, 061 specimens analysed, 160 were positive for GHB (1.1% of all cases, range 0.4–1.8%). GHB positive drivers were 66.9% male (33.1% female) and had an average age of 32 years. The mean GHB concentration identified was 89 mg/kg (range 6–354 mg/kg). GHB was found to be closely associated with amphetamine type substances (ATS), particularly methylamphetamine. Though GHB was present in only 2.2% of all ATS positive specimens submitted to the laboratory, 91.2% of all GHB positive cases contained an ATS. Other drugs commonly co-administered with GHB were THC, cocaine, benzodiazepines and erectile dysfunction drugs. GHB was found to be more commonly identified in drivers from city areas and a geographical localisation of the use of the drug was identified in the Gold Coast region of Queensland.